Discovery of Unusual Biaryl Polyketides by Activation of a Silent Streptomyces venezuelae Biosynthetic Gene Cluster - Thanapipatsiri, Anyarat (Chembiochem, 2016)
Comparative transcriptional profiling of a ΔbldM mutant of Streptomyces venezuelae with its unmodified progenitor revealed that the expression of a cryptic biosynthetic gene cluster containing both type I and type III polyketide synthase genes is activated in the mutant. The 29.5 kb gene cluster, which was predicted to encode an unusual biaryl metabolite, which we named venemycin, and potentially halogenated derivatives, contains 16 genes including one—vemR—that encodes a transcriptional activator of the large ATP‐binding LuxR‐like (LAL) family. Constitutive expression of vemR in the ΔbldM mutant led to the production of sufficient venemycin for structural characterisation, confirming its unusual biaryl structure. Co‐expression of the venemycin biosynthetic gene cluster and vemR in the heterologous host Streptomyces coelicolor also resulted in venemycin production. Although the gene cluster encodes two halogenases and a flavin reductase, constitutive expression of all three genes led to the accumulation only of a monohalogenated venemycin derivative, both in the native producer and the heterologous host. A competition experiment in which equimolar quantities of sodium chloride and sodium bromide were fed to the venemycin‐producing strains resulted in the preferential incorporation of bromine, thus suggesting that bromide is the preferred substrate for one or both halogenases.